Automatic defense against zero-day polymorphic worms in communication networks - Mohammed, Mohssen, 1982- (Information security books, 2013)
"A computer worm is a kind of malicious program that self-replicates automatically and quickly to compromise the security of a computer network. A polymorphic worm is able to change its payload in every infection attempt thereby forcing constant changes to ward off the attacks. Whenever a novel worm is detected in the Internet, the common approach is that the experts from security community analyze the worm code manually and produce a signature. The alternative approach is to find a way to automatically generate signatures that are relatively faster to generate and are of acceptable good quality. This book focuses on how we can automatically generate signatures for unknown polymorphic worms"--